Pelatihan Kewirausahaan Wanita Nelayan dalam Pengolahan Ikan Di Kelurahan Ulak Karang - Yaswinda Yaswinda; Elida Elida; Yelva Nofriyanti; Yolanda Intan Sari (Universitas Negeri Padang, 2020)
This community service is motivated by the lack of optimal utilization and understanding of the community in managing marine products in the coastal area. One of the marine products that has high protein is fish, but its processing has not been developed much. This community service activity was carried out in Ulak Karang Selatan, Padang city. The subjects in this study were fisherwomen of Ulak Karang Selatan. This service was carried out in May-July 2020. The methods carried out were lectures, direct practice and mentoring. The results show that there is community enthusiasm for the training. Most of the participants were able to make their own fish dishes. Although the shape of the product is not optimal, it is very good in terms of taste.